2021
DOI: 10.1007/s00421-021-04672-x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of VO2 kinetics in kidney transplant recipients

Abstract: Purpose Aerobic exercise capacity is reduced in patients with chronic kidney disease, partly due to alterations at the muscular and microvascular level. This study evaluated oxygen uptake (VO2) kinetics as indicator of muscular oxidative metabolism in a population of Kidney Transplant Recipients (KTRs). Methods Two groups of KTRs enrolled 3 (n = 21) and 12 months (n = 14) after transplantation and a control group of healthy young adults (n = 16) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…It has recently been reported that patients with RTx on average have a higher VO 2 peak at 1‐year follow‐up as compared with 3 months post‐transplant 13 . The observed VO 2 peak in these populations at both the 3 months (1.4 L/min) and at 12 months (1.9 L/min) were significantly higher than those observed in our patients at baseline and 3‐year follow‐up.…”
Section: Discussioncontrasting
confidence: 62%
“…It has recently been reported that patients with RTx on average have a higher VO 2 peak at 1‐year follow‐up as compared with 3 months post‐transplant 13 . The observed VO 2 peak in these populations at both the 3 months (1.4 L/min) and at 12 months (1.9 L/min) were significantly higher than those observed in our patients at baseline and 3‐year follow‐up.…”
Section: Discussioncontrasting
confidence: 62%
“…Cardiopulmonary exercise testing (CPET) is currently recognized as a useful clinical tool to assess the physical fitness and exercise limitations of patients with cardiac, pulmonary and musculoskeletal diseases [1][2][3]. Its value has been demonstrated in the prevention and prognostic monitoring of cardiovascular diseases, in the prescription and follow-up of exercise training interventions and in the evaluation of medical treatment measures [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a CPET evaluation has an important role in driving clinical decisions in end-stage heart or lung disease, guiding the selection process of candidates for transplantation [4]. However, the current body of evidence about CPET is mainly focused on the exercise response [2,3]; fewer studies have investigated the behavior of respiratory gas indices during recovery after maximal exercise testing especially in clinical populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of control technology, the CRP responses to exercise can be described as a single-input/single-output system (i. e. WR-CRP). The description of these systems allows to identify the influence of factors such as type of exercise (Koschate et al 2019a , b ), ambient conditions (Drescher et al 2018 ) and individual characteristics, e. g. age (Koschate et al 2016a , b ; Ebine et al 2018 ; Patti et al 2021 ) or fitness (Beltrame et al 2020 ; Inglis et al 2021 ), on the regulation of the cardiorespiratory system. From the individual kinetics and other characteristics of regulation, interventions, e. g. exercise prescriptions for athletes and patients, can be defined.…”
Section: Introductionmentioning
confidence: 99%